RADIO RIA FM SEBAGAI MEDIA SIAR BAGI KELUARGA DAN KAUM WANITA - Kartika Sari, Irene; ., Ramadhian; Anggitia, Paramastu Titis (KOMUNITAS, 2014)
Radio is an auditory medium or media that can only be heard, and can be brought cheap populist or heard anywhere. Radio as a medium has the greatest power of imagination because the media is blind to  visualize  the  voice  announcer  or  factual  information  through  the  listeners  ear.  Broadcasting program is very important for the implementation ofa radio broadcast. In this research the authors are  using  theory  by  Rhenald  Kasali  (1999),  to  be  able  to  know  the  stage  of  broadcast  program conducted by Ria FM radio. The broadcasting programcomponents include segmentation, targeting, formatting, programming. This research uses descriptive qualitative method,  to determine the broadcast program conducted by Ria FM radio with audience segmentation family and women. The  research  showed  that  the  presence  of  the  broadcast  media  for  women  ,  does  not  remove  the listener from the men who are included in the family . as well as broadcasting programs that support to families , ranging from children to the elderly can all join in a program broadcast on Ria FM radio. The fourth component into the program broadcast on FM radio Ria include stages of segmentation, targeting , formatting , programming . Segmentationis determined through the marketing process , the needs of listeners , and the productive age group that can be heard by anyone . Targeting the show is determined by the content can also be determined through such interactive pathways , sms , facebook , twitter , and through the quiz . Formatting has been determined from the beginning Ria FM joined the production team of Sonora and Ria FM live only running it alone . Programming , ranging from the type of program , program schedules, and its relationship with advertisers all done with the idea of the producer and the other production team .